Contrasting Impacts of Climate Warming on Coastal Old-Growth Tree Species Reveal an Early Warning of Forest Decline - Mercer, Catherine; Comeau, Vanessa M.; Daniels, Lori D.; Carrer, Marco (Frontiers in Forests and Global Change, 2022)
Old-growth forests in the Pacific Northwest are being fundamentally altered by climate change. A primary example of this is yellow-cedar (Callitropsis nootkatensis), a culturally and economically important species, which has suffered widespread decline across its range since the beginning of the twentieth century. We used tree rings to compare the climate-growth response of yellow-cedar to two co-occurring species; western hemlock (Tsuga heterophylla) and Sitka spruce (Picea sitchensis), in an old-growth forest on Haida Gwaii, Canada, to better understand the unique climatic drivers of a species that is declining across its range. We developed three species-specific chronologies spanning 560–770 years, reconstructing a long-term record of species growth and dynamics over time. The climate is strongly influenced by the Pacific Decadal Oscillation (PDO), a multi-decadal pattern of ocean-atmospheric climate variability. Climate varied across three time periods that have coincided with major shifts in the PDO during the twentieth century [1901–1945 (neutral/positive), 1946–1976 (negative) and 1977–2015 (positive)]. Conditions were significantly warmer and wetter during positive phases, with the greatest maximum temperatures in the most recent period. We used complimentary methods of comparison, including Morlet wavelet analysis, Pearson correlations, and linear-mixed effects modeling to investigate the relations between climate and species growth. All three species exhibited multi-decadal frequency variation, strongest for yellow-cedar, suggesting the influence of the PDO. Consistent with this, the strength and direction of climate-growth correlations varied among PDO phases. Growing season temperature in the year of ring formation was strongly positively correlated to yellow-cedar and western hemlock growth, most significantly in the latter two time periods, representing a release from a temperature limitation. Sitka spruce growth was only weakly associated with climate. Yellow-cedar responded negatively to winter temperature from 1977 to 2015, consistent with the decline mechanism. Increased yellow-cedar mortality has been linked to warmer winters and snow loss. This study provides new insights into yellow-cedar decline, finding the first evidence of decline-related growth patterns in an apparently healthy, productive coastal temperate rainforest.